La restauration-conservation (2011-2019) de la Fondation Vasarely (1973-1976), ou comment rendre actuelles des ambiances surannées - Ana Bela de Araujo (Ambiances)
In 1973, the artist Victor Vasarely turned architect by building the Foundation, an architectonic centre which was to bear his name, in Aix-en-Provence. This singular architectural manifestation of optical art challenges us by its envelope as much as by its interior: a monument in black and white on the outside versus an explosion of colour, thanks to 42 monumental works, Integrations by Vasarely. Forty years after its construction, the building has aged, but its authenticity can be restored. Conservation and restoration measures have been under way since 2011. The building was listed in 2003, then classified as a historic building in 2013. Making this emblematic work of Les Trente Glorieuses, the thirty “glorious” years between 1945 and 1975, part of our heritage is questioned. Is it a question of restoring the building’s internal and external material qualities, or is it above all the spirit of the place that counts? For a building whose characteristic is to be a machine with illusions, is it possible to reproduce visitors’ perceptual and behavioural responses identically? To question the sensory dimension of the restoration / conservation of the Foundation amounts here to probing the ambiguous concept of “heritage ambiance”.